Selam: online thrift shopping platform / Naqiuddin Irham Mohd Yusri ... [et al.] - Mohd Yusri, Naqiuddin Irham; Mudzarffar, Nor Faraha Atika; Ahmad Yani, Nur Ain Atiliah; Jamsari, Muhammad Nabil Ziqri; Yazeed, Muhammad Zulhilmi; Murad, Khairudin (2022)
Nowadays, with the advancement of technology, everything can easily be attained from the palm of our hands, or to be precise, from our phones. This refers to the number of applications that serve multiple purposes in everyone's life. Currently, online and thrift shopping are on the rise in Malaysia. We found that thrifting has become a trend in Malaysia and with the help of online shopping, it would give consumers a hassle-free shopping experience. Therefore, Selam application was developed to connect these two things together and it will exclusively focus on thrift or second-hand clothes. This paper will explain how the application works and develops into what it aims to be. For this project, we applied the AIDA Model for a clearer understanding.